Russia in the Conditions of Geopolitical Projects Dictatorship - Alexander Ivanovich Kugay (Управленческое консультирование, 2018)
This article analyzes the nature of the geopolitical challenges faced by Russia. Tool of unprecedented political and economic pressure on Russia is the theory and practice of repressive social projects aimed at reformatting nations, states, formed not on the draft United States and its satellites. Today, the main reproach of the radical opposition political course of present-day Russia is expressed in the fact that we do not keep up with the countries of “advanced democracy.” The point here is that the majority of states in the modern world has no real sovereignty. Even developed Western countries that have joined because of the situation in Ukraine to the US campaign against Russia against its own vital interests, demonstrated that such sovereignty do not have and can be considered, if not as occupied territory of America (which, by the way, if you remember the geography of placing US bases beyond their own borders, it is true in the literal sense of the word), then as political colonies are vassals of Washington. The US State Department claims imperative “What’s good for the US is good for the world.” Hence today in the EU is important, not the truth, but that the United States believes the truth. American project “Ukraine” is aimed at impeding the implementation of the natural integration processes in the CIS, and reformatting the weakening of Russia, its displacement from the EU market, with the countries which Russia has established mutually beneficial economic relations. Russia will stand and will achieve even greater recognition in the world, if the world will be common to all mankind Project Truth, which, ultimately, the authors are interested and anti-Russian project, as the only truth, including the right of peoples and nations to self-determination, can be the basis of an adequate world order calls XXI century.